Предмет: Алгебра,
автор: лариса20021
упростить выражение (3a+b)*(2d-5b)-6(d-b) это в квадрате.
Ответы
Автор ответа:
0
6ad-15ab-6(d в квадрате -2db + b в квадрате)= 6ad-15ab-6d в квадрате +12db -6b в квадрате = (6ad+12db-6d)-(15ab-6b)= 6d(a+2b-1)-(15ab-6b)= 6ad+12ab-6d-15ab+6b= 6ad-3ab-6d+6b= (6ad-3ab)-(6d-6b)
Вроде бы так
Похожие вопросы
Предмет: Русский язык,
автор: alishanismailov6
Предмет: Математика,
автор: muqamedkarimaiaru
Предмет: Информатика,
автор: n52385ka
Предмет: Обществознание,
автор: maska99
Предмет: Математика,
автор: margoshaavgyst